Tryptophan metabolism activation by indoleamine 2,3-dioxygenase in adipose tissue of obese women: an attempt to maintain immune homeostasis and vascular tone - Wolowczuk, Isabelle; Hennart, Benjamin; Leloire, Audrey; Bessede, Alban; Soichot, Marion; Taront, Solenne; Caiazzo, Robert; Raverdy, Violeta; Pigeyre, Marie; Guillemin, Gilles J.; Allorge, Delphine; Pattou, François; et al. (American journal of physiology. Regulatory, integrative and comparative physiology, 2012)
Human obesity is characterized by chronic low-grade inflammation in white adipose tissue and is often associated with hypertension. The potential induction of indoleamine 2,3-dioxygenase-1 (IDO1), the rate-limiting enzyme in tryptophan/kynurenine degradation pathway, by proinflammatory cytokines, could be associated with these disorders but has remained unexplored in obesity. Using immunohistochemistry, we detected IDO1 expression in white adipose tissue of obese patients, and we focused on its contribution in the regulation of vascular tone and on its immunoregulatory effects. Concentrations of tryptophan and kynurenine were measured in sera of 36 obese and 15 lean women. The expression of IDO1 in corresponding omental and subcutaneous adipose tissues and liver was evaluated. Proinflammatory markers and T-cell subsets were analyzed in adipose tissue via the expression of CD14, IL-18, CD68, TNFα, CD3ε, FOXP3 [a regulatory T-cell (Treg) marker] and RORC (a Th17 marker). In obese subjects, the ratio of kynurenine to tryptophan, which reflects IDO1 activation, is higher than in lean subjects. Furthermore, IDO1 expression in both adipose tissues and liver is increased and is inversely correlated with arterial blood pressure. Inflammation is associated with a T-cell infiltration in obese adipose tissue, with predominance of Th17 in the omental compartment and of Treg in the subcutaneous depot. The Th17/Treg balance is decreased in subcutaneous fat and correlates with IDO1 activation. In contrast, in the omental compartment, despite IDO1 activation, the Th17/Treg balance control is impaired. Taken together, our results suggest that IDO1 activation represents a local compensatory mechanism to limit obesity-induced inflammation and hypertension.